Application of Foozma Therapy (Foot Massage Using Olive Oil) to Reduce Pain in Mothers after Cesarean Section - Arvinda Dwi Nugraheni; Sulastri Sulastri (Indonesian Journal of Global Health Research, 2026)
Post cesarean section procedures can cause pain sensations. Pain management involves a combination of self-care interventions and non-pharmacological foot massage therapy, which is safe and easy to administer. To improve circulation, reduce pain, relax muscles, and provide comfort to the patient. Foot massage therapy includes techniques such as effleurage (stroking), petrissage (kneading), tapotement (tapping), friction (rubbing), and vibration (vibrating).  In the case study of foot massage for post-cesarean section mothers, data was collected through direct observation and measurement of pain intensity using a Numeric Rating Scale (NRS) questionnaire. The assessment was conducted through interviews and observation of the patient's condition before and after foot massage therapy. Data analysis was performed descriptively by comparing pain scores before and after foot massage intervention to see changes in pain intensity experienced by patients. The results of the foot massage on the respondents over two consecutive days showed a decrease in pain levels from a score of 6 (moderate pain) to a score of 2 (mild pain). The application of foot massage therapy can help reduce pain experienced by post-cesarean section mothers.